2015
DOI: 10.1371/journal.pone.0138492
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Prevalence of Rheumatic Diseases in Shantou, China, in the Past Three Decades: A COPCORD Study

Abstract: This study aimed to clarify changes in the prevalence of rheumatic diseases in Shantou, China, in the past 3 decades and validate whether stair-climbing is a risk factor for knee pain and knee osteoarthritis (KOA). The World Health Organization-International League Against Rheumatism Community Oriented Program for Control of Rheumatic Diseases (COPCORD) protocol was implemented. In all, 2337 adults living in buildings without elevators and 1719 adults living in buildings with elevators were surveyed. The preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by systemic inflammation, persistent synovitis and joint destruction. The prevalence of RA in mainland China is estimated to range from 0.2% to 0.9% and is comparable with worldwide prevalence estimates (0.24%) …”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by systemic inflammation, persistent synovitis and joint destruction. The prevalence of RA in mainland China is estimated to range from 0.2% to 0.9% and is comparable with worldwide prevalence estimates (0.24%) …”
Section: Introductionsupporting
confidence: 61%
“…Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by systemic inflammation, persistent synovitis and joint destruction. The prevalence of RA in mainland China is estimated to range from 0.2% to 0.9% [1][2][3] and is comparable with worldwide prevalence estimates (0.24%). 4 RA represents a significant health and socioeconomic burden, and affects all domains of health-related quality of life (HRQoL).…”
Section: Introductionmentioning
confidence: 58%
“…The World Health Organization‐International League Against Rheumatism COPCORD protocol was implemented in a study in China to clarify changes in the prevalence of rheumatic diseases in Shantou, China, in the past three decades . In all, 4056 adults were surveyed.…”
Section: Discussionmentioning
confidence: 99%
“…The 11 included cross-sectional studies reported the AS prevalence rates and sample sizes, which were combined for an effect size analysis [18][19][20][21][22][23][24][25][26][27][28]. The heterogeneity test revealed a P < 0.1 and I 2 > 50%, therefore, a random effects model was adopted for the meta-analysis.…”
Section: Overall Prevalence In Chinamentioning
confidence: 99%
“…To ensure the reliability of the data, this study was not included in the subgroup analysis of the prevalence of AS by sex. Thus, ten studies were ultimately involved in the analysis [25] 2006.07 English Cross-sectional study New York criteria (1984) 9 Dong et al [26] 2006.04 Chinese Cross-sectional study New York criteria (1984) 9 Wang et al [27] 2013.03 Chinese Cross-sectional study New York criteria (1984) 6 Wang et al [28] 2011.08 Chinese Cross-sectional study New York criteria (1984) 8 Community of sex differences in the prevalence of AS [18][19][20][21][22][23][24][25][26]28]. A random effects model was used for meta-analysis because of heterogeneity, the results showed that the prevalence of AS in males was 0.42% (95% CI 0.31%, 0.52%).…”
Section: Prevalence Of As Between Males and Females In Chinamentioning
confidence: 99%